Peran Malaikat Dalam Mendukung Konsep Keseimbangan Hidup Modern - Raka Noviandri Ramadhan; Muhammad Haikal Hodila; Ikhsan Al Khifari; Aman Dariyanti; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Modern life balance is an increasingly complex challenge in the era of globalization and digitalization. Amidst the pressures of work, social life, and spiritual needs, the concept of angels in religious traditions offers a unique perspective for understanding the harmony of life. This research aims to explore the symbolic and spiritual role of angels in supporting the concept of balance in modern life, both personally and socially. The approach used in this research is a qualitative method with literature analysis and in-depth interviews with individuals from various religious and cultural backgrounds.but also as a symbol of moral and spiritual inspiration that is relevant to the challenges of modern life. Respondents revealed that belief in angels provides a sense of peace, motivation to act better, and awareness of social responsibility. In a modern context, angels are considered a reminder of the importance of harmony between the material and spiritual dimensions of life.This research concludes that the concept of angels can be a relevant approach in supporting the balance of modern life, both as an inspiration for spiritual values ​​and as a symbol of moral motivation in facing the dynamics of contemporary life. These findings contribute to the study of modern spirituality and open opportunities for further discussion about how religious elements can contribute to human well-being in the modern.